Structural Changes in HPRT Gene of V79 Cells After Irradiation With Heavy Ions—Immediate and Delayed Effects - Bláha, Pavel; Koshlan, Igor V.; Koshlan, Nataliya A.; Bogdanova, Yulia V.; Petrova, Daria V.; Govorun, Raisa D.; Múčka, Viliam; Krasavin, Evgeny A. (Frontiers in Physics, 2021)
The radiobiological effects of accelerated ions with high-charge and high-energy (HZE) on mammalian cells and their propagation in time are still not sufficiently explained and attract great deal of attention. This work aims to compare the immediate and delayed effects with emphasis on the latter. As shown by our group, the dependence of mutant fraction on expression time after irradiation may have interesting, non-monotonic, character depending on LET (linear energy transfer) of the used heavy ions. We speculate that this phenomenon may occur due to the induced genomic instability. Another area of our research is study of the DNA structural changes in these mutants induced at different ET. Chinese hamster V79 cells were irradiated with accelerated ions B-11, O-18, Ne-20, and gamma radiation. The LET was ranging from 0.23 keV/µm of Co-60 gamma rays up to 136 keV/µm of Ne-20 ions. DNA of unique HPRT mutants was isolated, concentration measured, HPRT exons amplified, and analyzed at several different time points, up to about 40 days, after exposure. Over 1200 HPRT mutants were analyzed for deletions of exons and sorted into three main categories: partial deletion, PD – with deletion of 1 – 8 exons; total deletions, TD – with all 9 exons deleted; no deletions – no change in HPRT structure observed. In general, number of samples with partial deletion was increasing with LET of the used radiation, suggesting that higher energy deposition to the cell nucleus is more likely to cause larger structural changes. In the case of total deletions, increase in their number with LET was observed up to LET 115 keV/µm followed by a sharp decrease. The samples were also analyzed for the distribution of deletions in particular exons at various expression times, so called mutational patterns. Hypothesis of the mechanisms behind observed phenomena is given and possible implications for further research are discussed.